Mechanism of Qingchang Suppository on repairing the intestinal mucosal barrier in ulcerative colitis - Shan, Jingyi; Liu, Suxian; Liu, Haoyue; Yuan, Jianye; Lin, Jiang (Frontiers in Pharmacology, 2023)
Ulcerative colitis (UC) is a refractory inflammatory bowel disease and the outcomes of conventional therapies of UC, which including 5-aminosalicylic acid, hormones, immunosuppressants, biological agents, etc. are not satisfied with patients and physicians with regard to psychological disturbance and financial burden. The abnormality of intestinal mucosal barrier in the pathogenesis of UC has been verified. Qingchang suppository (QCS) is an herbal preparation and its effective in treating ulcerative proctitis. The mechanism of QCS and its active components have not been concluded especially in mucosal healing. This review elucidated the potential mechanism of QCS from the intestinal mucosal barrier perspective to help exploring future QCS research directions.